META-ANALYSIS OF THE EFFECT OF USING PROBLEM SOLVING MODELS ON HIGH SCHOOL PHYSICS LEARNING ON STUDENT LEARNING OUTCOMES - DEA WIDYA SARI (PILLAR OF PHYSICS EDUCATION, 2022)
One that affects student learning outcomes is the learning model used. Experts have developed several learning models, one of which is a problem solving learning model, and there has been much research that looks at how the impact of problem solving models on student learning outcomes, but there has been no research that concludes how the impact of problem solving models on student learning outcomes. Therefore, meta-analysis methods are used. Meta-analysis is a method that analyzes some of the most important similar articles to conclude. This research purpose to decide the summary effect (M) of the impact of the use of problem solving models on high school physics learning on student learning outcomes and to determine the summary effect of the impact of the use of problem solving models on high school physics learning on student learning outcomes pursuant to subject matter. The sample in the study was twenty one articles from national journals. The result of this study is that there is an impact of the use of problem solving models in high school physics learning on student learning outcomes with a summary effect (M) of 0.812 which is in the high category and the second result is the application of problem solving models in high school physics learning has the highest influence on the kinematics motion material class x with a summary effect (M) of 1,670 which is in the very high category.